Fatigue in children and adolescents perinatally infected with human immunodeficiency virus: an observational study - A. M. ter Haar; M. M. Nap-van der Vlist; M. Van den Hof; S. L. Nijhof; R. R. L. van Litsenburg; K. J. Oostrom; D. Pajkrt (BMC, 2021)
Abstract Background Fatigue is common among adults living with human immunodeficiency virus (HIV) as well as children with a chronic disease (CCD). Fatigue can have disastrous effects on health status, including health related quality of life (HRQOL). Even so, fatigue is underexplored in children and adolescents perinatally infected with HIV (PHIV+) in the Netherlands. The objective of this observational study is to explore fatigue in PHIV+ and its association with their HRQOL. Methods We measured HRQOL and fatigue using the Pediatric Quality of Life Inventory™ (PedsQL 4.0) and the PedsQL Multidimensional Fatigue Scale (MFS). The PedsQL MFS encompasses three subscales: general fatigue, sleep/rest fatigue and cognitive fatigue, and a total fatigue score. We compared outcomes of PHIV+ children and adolescents in the Amsterdam University Medical Centre with three groups: 1) HIV-uninfected controls (HIV-) matched for age, sex, region of birth, socioeconomic status and adoption status, 2) CCD, and 3) the general Dutch population. Within the PHIV+ group we explored associations between fatigue and HRQOL. Results We enrolled 14 PHIV+ (median age 10.2 years [IQR 9.2-11.4]) and 14 HIV-. Compared to CCD, PHIV+ significantly reported less general fatigue (mean difference 13.0, 95% CI 1.3 to 24.8). PHIV+ did not score significantly different on any of the other PedsQL MFS scales compared to HIV-, CCD or the general Dutch population. PHIV children scored relatively low on the cognitive fatigue scale in comparison to HIV-uninfected matched controls, CCD and the general population, although these differences did not reach significance. Among PHIV+, a lower score on total fatigue, general fatigue and cognitive fatigue was associated with a lower HRQOL score. Conclusions The results of this study suggest that PHIV children and adolescents do not experience more symptoms of fatigue than their healthy peers. However, PHIV children and adolescents may be more likely to experience cognitive fatigue. Fatigue in PHIV also appears to be associated with children's HRQOL. Further research should confirm these exploratory findings.